Preliminary observations of glucose metabolism dysregulation in pediatric Huntington’s disease - Graziola, Federica; Danti, Federica Rachele; Penzo, Martina; Spagarino, Antonio; Minacapilli, Eleonora; Moscatelli, Marco; Zibordi, Federica; Mariotti, Caterina; Zorzi, Giovanna (Frontiers in Neurology, 2025)
BackgroundPediatric Huntington’s disease (PHD), a rare and severe form of juvenile-onset Huntington’s disease (JOHD), is associated with highly expanded CAG repeats in the HTT gene and a rapidly progressive neurodegenerative course. Recent studies have suggested that glucose metabolism may be impaired in PHD due to reduced expression of glucose transporters in the brain, resembling aspects of GLUT1 Deficiency Syndrome (GLUT1DS).MethodsWe investigated glucose metabolism in two pediatric patients with genetically confirmed PHD (CAG repeats: 76 and 79) referred to our tertiary care center. Clinical, neuroimaging, and neuropsychological data were collected alongside metabolic assessments, including cerebrospinal fluid (CSF) and plasma glucose and lactate levels, CSF-to-serum glucose ratio, and red blood cell GLUT1 expression using the METAglut1 test. 18F-FDG PET imaging and brain MRI were performed to assess cerebral metabolism and structural changes.ResultsBoth patients exhibited progressive motor and cognitive decline with dystonia-parkinsonian features, learning disabilities, and behavioral disturbances. Brain MRI showed caudate and putaminal atrophy, while PET imaging demonstrated severely reduced glucose uptake in the basal ganglia. CSF/plasma glucose ratios were within or near the lower end of the normal range (0.51 and 0.6), and GLUT1 expression in red blood cells was within normal limits. No significant biochemical alterations consistent with GLUT1DS were detected.ConclusionOur findings confirm localized cerebral hypometabolism in the basal ganglia of PHD patients, consistent with previous neuropathological reports. However, systemic biochemical indicators of glucose transport deficiency, including erythrocyte GLUT1 function and CSF glucose, were not significantly altered. While glucose dysregulation appears to be a feature of PHD brain pathology, our results do not support the use of metabolic interventions such as the ketogenic diet in the absence of confirmed GLUT1 dysfunction. Further studies in larger cohorts are warranted to better characterize the metabolic profile of PHD and guide therapeutic strategies.